Pillar[5]arene Based [1]rotaxane Systems With Redox-Responsive Host-Guest Property: Design, Synthesis and the Key Role of Chain Length - Zhang, Runmiao; Wang, Chenwei; Long, Renhua; Chen, Tingting; Yan, Chaoguo; Yao, Yong (Frontiers in Chemistry, 2019)
Pillar[n]arenes are a new type of macrocyclic compounds, which were first reported in 2008 by Ogoshi. They not only have cylindrical, symmetrical and rigid structures, but also have many advantages, including easy functionalization and rich host-guest properties. On the other hand, mechanically interlocked molecules (MIMs) exist extensively in nature which have been artificially synthesized and widely applied in the fields of nanotechnology and biology. Although pillar[5]arenes based MIMs have been investigated a lot recent years, pillar[5]arene based [1]rotaxanes are very limited. In this report, we synthesized a series of amide-linked pillar[5]arene-based [1]rotaxanes with ferrocene unit as the stopper. Under the catalysis of HOBT/EDCL, the mono-amido-functionalized pillar[5]arenes were amidated with ferrocene carboxylic acid to constructed ferrocene-based [1]rotaxanes, respectively. The structure of the [1]rotaxanes were characterized by 1H NMR, 13C NMR, 2D NMR, mass spectroscopy and single-crystal X-ray structural determination. In the experiment, the monofunctionalized pillar[5]arene we synthesized with a self-inclusion property, which forming a pseudo-rotaxane, the key role is the length of the imine chain in this process, formed a rotaxane through amidation of ferrocene dicarboxylic acid which acting as a plug. In addition, due to the ferrocene units, the pillar[5]arene-based [1]rotaxanes perform electrochemically reversible property. Based on this nature, we hope these pillar[5]arene-based [1]rotaxanes can be applied in battery devices in future.